Using Fast Phonic Program To Learn Reading Skills - Faradiba Sari Harahap (Universitas Pahlawan Tuanku Tambusai, 2023)
This research reviews the use of fast phonics to learn reading skills with phonics for emergent and early readers. This research is a descriptive qualitative. Observation is used as the main instrument to collect data. The data uses the app of Reading Eggs that contains Fast Phonics program as the object of research. The analysis of the data uses three ways of qualitative analysis, namely reducing data, displaying data, and conclusions. Fast Phonics is part of ABC Reading Eggs application— online reading program for ages two to 13—was developed by its team of highly experienced educators, animators and web developers. This phonics program helps students become a more fluent reader, as they'll be able to quickly and accurately recognize and pronounce words. The Fast Phonics program includes 20 fun‑filled levels (peaks) where students learn key phonics skills. This research will take Peak 1 as the sample of activities. The analysis shows that Fast Phonics program explicitly and systematically teaches, supports reinforces and assesses the core phonics skills, namely: letter sound-correspondence, blending, segmenting and syllable. Fast Phonics program also covers pseudo-words and decodable books and an accompanying end-of-book quiz in each peak. This complete synthetic phonics program is a dynamic mix of maps, upgrades and exciting learning activities. Since this program is an online learning, students in around the world may considered this program as a useful and practical learning tool to master key phonics skills and improve reading skills. Keywords: Phonics, Reading Skill, Fast Phonics